Aerospace series. Cable outlet accessories for circular and rectangular electrical and optical connectors. Cable outlet, style K, 90°, for heat shrinkable boot, shielded, sealed, self-locking. Product standard Part 062, (13th May 2022) - British Standards Institution,
No abstract available